Chinese ethnic minorities and learner identity in non-autonomous schools: a systematic review - Yang, Leyao; Liu, Yan; Zhuang, Zhixian (Frontiers in Education, 2025)
This systematic review investigates existing research on how ethnic minority students in China construct their identities within the “Inland Ban (Inland Class)1” at various educational levels. A structured search was conducted exclusively on English-language journals using the Web of Science (WoS) database from the Sheffield Hallam University Library between July and August 2023. A total of 693 articles were initially identified, and after rigorous screening, 13 studies met the inclusion criteria. Studies were selected based on their focus on Chinese ethnic minorities, identity construction, and educational experiences in the inland class between 2000 and 2023. Exclusion criteria included studies not focused on ethnic minority students, those examining teachers instead of students, research on language policies rather than identity, and inaccessible full texts. Each selected study was analyzed for its focus on ethnic groups and languages, sample size, educational level, location of the host school, and research methodology. While this study primarily examines identity construction, it acknowledges that pedagogical methods, curriculum content, and language policies in Neidi Ban schools may also influence students’ self-perceptions and national identity formation. The review highlights key factors shaping identity construction, including linguistic challenges, cultural disparities, and institutional practices. A post-structuralist lens explores how identities are shaped within hierarchical power structures, particularly in Mandarin-dominant environments. Additionally, Bourdieu’s theories of cultural, social, and symbolic capital provide a framework for understanding how minority students adapt and renegotiate their identities in Han-centric educational settings.